How different health literacy dimensions influences health and well‐being among men and women: The mediating role of health behaviours - Fan Zhang; Peggy P. L. Or; Joanne W. Y. Chung (Wiley, 2021)
Abstract Background Health literacy, the ability to access, understand, evaluate and apply health information, was found to contribute to positive health outcomes, possibly via promoting healthy behaviours. However, the specific pathways linking different health literacy skills to health and well‐being have remained unclear. Methods A cross‐sectional survey with structural questionnaires was administered among 2236 adults in Hong Kong (mean age = 46.10 ± 19.05). Health literacy was measured by HLS‐Asian‐47. Participants' physical conditions and subjective well‐being were predicted by health literacy and health behaviours with structural modelling path analysis. Results Health literacy in finding and understanding information showed a direct effect on enhancing physical health, while applying information capacity had an indirect positive effect via promoting health behaviours, which was moderated by sex. Only among women, this indirect effect predicting fewer physical symptoms and better well‐being was significant. Conclusions Different health literacy dimensions showed distinct direct and indirect pathways in influencing health for men and women. Based on the findings, skill trainings should be developed to enhance both gender's abilities of finding and understanding health information, while the ability of applying health information should also be improved for modifying lifestyle and promoting health, particularly for women. Patient or Public Contribution Two thousand and two hundred thirty‐six adults from different districts of Hong Kong participated in the study, and responded to questions on health literacy, behaviours and health status.